Perbandingan Performa dari Algoritma AES dan RSA dalam Keamanan Transaksi - Ahmad Miftah Fajrin; Christoper Kelvin; Brian Owen; Bayu Aji (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
Online transactions have become increasingly prevalent in the modern day. It is highly user-friendly and can be conveniently transported to any location. Nevertheless, internet transactions possess inherent security vulnerabilities that render them susceptible to assaults, hence enabling the retrieval of consumers' personal data. Hence, it is imperative to use encryption measures for safeguarding users' personal data, including PINs, CVVs, and card numbers. This study aims to evaluate and contrast the efficacy of AES and RSA algorithms within a website platform designed for online transactions. The study's findings indicate that there is minimal disparity in the performance of the two algorithms. However, it was observed that both algorithms exhibit enhanced security when employing longer keys.